Associations between visual function and magnitude of refractive error for emmetropic to moderately hyperopic 4‐ and 5‐year‐old children in the Vision in Preschoolers ‐ Hyperopia in Preschoolers Study. (27th March 2021) - Ciner, Elise B; Kulp, Marjean Taylor; Pistilli, Maxwell; Ying, Gui‐Shuang; Maguire, Maureen; Candy, T Rowan; Moore, Bruce; Quinn, Graham
Abstract: Purpose: To evaluate associations between visual function and the level of uncorrected hyperopia in 4‐ and 5‐year‐old children without strabismus or amblyopia. Methods: Children with spherical equivalent (SE) cycloplegic refractive error of −0.75 to +6.00 on eligibility testing for the Vision in Preschoolers–Hyperopia in Preschoolers (VIP‐HIP) study were included. Children were grouped as emmetropic (<1D SE myopia or hyperopia), low hyperopic (+1 to <+3D SE) or moderate hyperopic (+3 to +6D SE). Children with anisometropia or astigmatism (≥1D), amblyopia or strabismus were excluded. Visual functions assessed were monocular distance visual acuity (VA) and binocular near VA with crowded HOTV charts, accommodative lag using the Monocular Estimation Method and near stereoacuity by 'Preschool Assessment of Stereopsis with a Smile'. Visual functions were compared as continuous measures among refractive error groups. Results: 554 children (mean age 58 months) were included in the analysis. Mean SE (SD) N for emmetropia, low and moderate hyperopia were +0.52D (0.49) N = 270, +2.18D (0.57) N = 171 and +3.95D (0.78) N = 113, respectively. There was a consistent trend of poorer visual function with increasing hyperopia ( p < 0.001). Although all children had age‐normal distance VA, logMAR (Snellen) VA of 0.00 (6/6) or better was achieved (distance, near) among more emmetropic (52%, 26%) and low hyperopic (47%, 15%) children than moderate hyperopes (25%, 9%). Mean (SD) distance logMAR VA declined from emmetropic 0.05 (0.10), to low hyperopic 0.06 (0.10) to moderately hyperopic children 0.12 (0.11) ( p < 0.001); A mild progressive decrease in near VA also was observed from the emmetropic 0.13 (0.11) to low hyperopic 0.15 (0.10) to moderate hyperopic 0.19 (0.11) groups, ( p < 0.001). Accommodative responses showed an increased lag with increasing hyperopia (ρ = 0.50, p < 0.001). Median near stereoacuity for emmetropes, low and moderate hyperopes was 40, 60 and 120 sec arc, respectively. The percentage of these groups with no reduced near visual functions was 83%, 61%, and 34%, respectively. Conclusions: Decreasing visual function was associated with increasing hyperopia in 4‐ and 5‐year‐olds without strabismus or amblyopia. As hyperopia with reduced visual function has been associated with early literacy deficits, near visual function should be evaluated in these children.